A STUDY OF CERVICAL LESIONS IN CORRELATION WITH HUMAN PAPILLOMAVIRUS ANALYSIS BY IMMUNOHISTOCHEMICAL ASSAY - NEERAJA, P; REDDY, C BHAKTHAVATSALA; KALAVATHI, C LAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: It has become clear that human papillomavirus (HPV) plays a critical role in the pathogenesis of nearly all cervical squamous cell carcinomas. Because HPV causes a variety of cervix lesions, including benign, premalignant, and malignant lesions, early detection of this infection benefits the patient. The goal of this study is to identify neoplastic and non-neoplastic cervix lesions, to study neoplastic and non-neoplastic cervix lesions caused by HPV in correlation with HPV analysis by immunohistochemistry (IHC), and to understand the significance of HPV in screening cervical lesions. Methods: The current study evaluated and compared HPV cocktail expression in 100 samples collected from 100 cases with cervical lesions. A semi-quantitative method was used to determine the positivity of the HPV cocktail. Comparison of expression of HPV cocktail IHC and histopathology was carried out. Results: Of the 100 cases, 30 were carcinoma cervix (CC), 4 were carcinoma in situ (CIS), 22 were squamous intraepithelial lesions (SIL), 20 were chronic cervicitis, 16 were chronic cervicitis with Koilocytic change, 7 were Koilocytic change, and 1 was Inflammatory polyp. SIL and CIS have a mean age of 46.8 and 44.5 years, respectively. There was a 42% incidence of carcinoma cases seen in the fourth decade, with a mean age of 45.9 years. The most common complaint presented by CC patients is AUB, with postmenopausal bleeding being the most common complaint. Seven patients with Squamous cell carcinoma present with postmenopausal bleeding. There were neoplastic lesions in 56% of the cases and non-neoplastic lesions in 44% of the cases. Premalignant cervix lesions include low grade squamous intra epithelial lesion, high grade squamous intra epithelial lesion, and CIS, which account for 46.42% of all cases. Non-neoplastic lesions such as chronic cervicitis account for 45.55% of all cases, followed by chronic cervicitis with Koilocytic change (36.36%), Koilocytic change (15.91%), and Polyp (2.27%). There were 28 Squamous cell carcinomas and 2 Adenocarcinomas among the 30 cases of CC. Squamous cell carcinoma accounted for 93.33% of all cases, while adenocarcinoma accounted for 6.67%. Moderately differentiated squamous cell carcinomas account for 86.66% of the cases, followed by well differentiated squamous cell carcinomas and poorly differentiated squamous cell carcinomas, which account for 6.66% of the cases. 26 (86.6%) of 30 squamous cell carcinomas tested positive for IHC. All two Adenocarcinoma cases (100%) and all CIS cases (100%) were positive. Out of the 22 SIL cases, 18 (81.81%) were positive. Out of 16 cases of chronic cervicitis with Koilocytic change, 14 (87.5%) were positive. Out of 20 chronic cervicitis cases, 12 (60%) were positive. 5 (71.43%) of the 7 cases of Koilocytic change were positive. Cervical lesions (benign, premalignant, and malignant) have a significant correlation with HPV cocktail IHC (p=0.01). Conclusion: The expression of the HPV cocktail was associated with clinical and histopathologic parameters in benign, premalignant, and malignant cervical lesions. Periodic follow-up allows patients to be better managed by providing vital data on the incidence of HPV infection in various cervical lesions. Low-grade SILs and high-grade SILs with HPV +ve infection can be monitored by HPV once a year instead of every 6 months. Patients over the age of 30 years with HPV-positive non-neoplastic cervical lesions can be monitored once every three years rather than annually. HPV is a biomarker for a better prognosis in cervical cancer, regardless of age, International Federation of Obstetricians and Gynecologists stage, or histologic type. HPV-positive tumors have a better prognosis.